The Role Of Corporate Brand Image And Service Quality On Client Satisfaction With Perceived Value As Mediating Variable (A Study In The Construction Of Civil Registration Service Building, Surakarta) - Ibnu Suryo; Asri Laksmi Riani (Universitas Sebelas Maret, 2016)
This research aims to understand the effect of brand image and service quality on employee’s satisfaction who is involved in the committee or Committee of Work Result Receiver (Panitia Penerima Hasil Pekerjaan - PPHP) in a construction project of civil registration service building in Surakarta, conducted by PT. Karsa Bayu Bangun Perkasa and PT. Surya Bayu Sejahtera, as well as to examine the role of perceived value as mediating variable. We distribute research questionnaires to 30 institution staffs. The data is examined using Structural Equation Model (SEM) to measure the role of corporate brand image and service quality with perceived value as mediating variable on client satisfaction. The result shows that corporate brand image has a significant direct effect on perceived value and client satisfaction, service quality also has a significant direct effect on perceived value and client satisfaction. Perceived value has a significant direct effect on client satisfaction. Meanwhile, corporate brand image has an indirect effect on client satisfaction through perceived value. However, service quality does not have an indirect effect on client satisfaction through perceived value, which means perceived value does not mediate the effect of service quality on client satisfaction.